2012
DOI: 10.1016/j.inhe.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the community about screening children for a multicentre malaria vaccine trial

Abstract: Community sensitisation, as a component of community engagement, plays an important role in strengthening the ethics of community-based trials in developing countries and is fundamental to trial success. However, few researchers have shared their community sensitisation strategies and experiences. We report on our perspective as researchers on the sensitisation activities undertaken for a phase II malaria vaccine trial in Kilifi District (Kenya) and Korogwe District (Tanzania), with the aim of informing and gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…[6,7]. Empirical studies have also suggested that for health research, the Ministry of Health (MoH) and other key health providers are often important key communities to include [8]. Even where there is clarity on which key communities to engage with, how representatives of those communities should be selected, and how researchers should work with those communities to ensure that their contribution is recognised but their independence from researchers is maintained, is far from straightforward [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6,7]. Empirical studies have also suggested that for health research, the Ministry of Health (MoH) and other key health providers are often important key communities to include [8]. Even where there is clarity on which key communities to engage with, how representatives of those communities should be selected, and how researchers should work with those communities to ensure that their contribution is recognised but their independence from researchers is maintained, is far from straightforward [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was agreed that the provision of health and other services and care could instead be considered as part of research design (including ancillary care) and benefit sharing. Even where CE is considered as primarily about communication, engagement activities can cover a wide range of interactions including those aimed at consulting with community members about what should be done in studies, through those aimed at sensitising community members about research or specific studies, to activities aimed at ensuring communities receive feedback of individual test results or overall study findings [8,10]. These activities are often part of formally organised communication strategies and activities of research institutions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relationships and conditions of great importance to health in different social worlds can be ignored if they do not easily fit into the universal statistical frameworks of evidence-based medicine and the institutional requirements of bioethics 2 5. In reports of research involving children, there is a lack of information on implementation processes, which would help in applying findings to different settings 6 7. Using qualitative methods, social scientists take up these matters with a commitment to widen the focus beyond ethics to ethos, that is, the study of values and perceptions as reflected in practice.…”
Section: Introductionmentioning
confidence: 99%